Enhanced acetone sensing performance of Au nanoparticles functionalized flower-like ZnO - Wang, Xin-jun; Wang, Wei; Liu, Yan-Li (Sensors and actuators. B, Chemical, 2012)
ZnO flowers functionalized by Au nanoparticles (NPs) with various Au contents have been developed. The gas sensing properties of the sensors fabricated from these materials were examined and compared at varied working temperatures. Improved sensor response, selectivity and short response and recovery times to acetone vapor were achieved by suitably modulating the weight percent of Au NPs. Experimentally, the formation of Au/ZnO hybrids and surface coarsening of ZnO flowers were found to lead to apparent further enhancement of the sensor performance.